Симулятор динамічних характеристик піроелектричного детектор - Бондаренко, О. Ю. (ХНУРЕ, 2020)
Dynamic characteristics, particularly, transient responses are considered. Specificities of transient responses when heated and cooled, are noted. Results applied to a simulator of a pyroelectric detector. The simulator plots transient responses. It allows to change a number of parameters to receive new results. The latter is important for not only modeling existing devices, but also designing new ones. Some applications of pyroelectric detectors are pointed. The simulator is free and can be used in labs at the Universities, or anywhere in the world.
Keywords: Піроелектричний детектор; Profilab Expert ver. 4.0.; вихідні електричні сигнали піроперетворювачів; симулятор роботи